Festschrift in honor of Dr. Jeffrey Hymes - Ketchersid, Terry; Chatoth, Dinesh K.; Kossmann, Robert J.; Mysayphonh, Chance; Kotanko, Peter; Maddux, Franklin W. (Frontiers in Nephrology, 2025)
This Festschrift in honor of Dr. Jeffrey Hymes, a distinguished leader in nephrology and a pioneer in the field of dialysis care. Dr. Hymes’ career has been marked by his unwavering commitment to improving patient outcomes through innovative approaches and data-driven insights. His contributions have not only advanced the practice of nephrology but have also had a profound impact on the lives of countless patients.